Managing Changes and Leadership Bagi Karyawan dan Manajerial Anara Airport Hotel Bandara Soekarno Hatta Tangerang - Suryawan, Ian Nurpatria; Prasastyo, Klemens Wedanaji; Sutrisno, Nuno (UKInstitute, 2022)
The training provided by the instructors from P3M Trisakti School of Management is to change the organizational culture to be superior and become a learning organization. Anara Hotel Bandara's employees and managers have committed to a management change process, namely unfreezing-movement-refreezing. The employees and managers of Anara Airport Hotel Soekarno Hatta Airport agreed to become an authentic organization, namely an organization that has behavior, structure, and processes, which are based on its ability to find authenticity in order to achieve the goals set by the Management of Anara Airport Hotel Soekarno Hatta Airport and are ready to face challenges. environmental changes and ready to transform into a superior individual and a leader who becomes a role model for other employees. Abstrak: Pelatihan yang diberikan oleh para instruktur dari P3M Sekolah Tinggi Ilmu Ekonomi Trisakti adalah merubah budaya organisasi menjadi unggul dan menjadi organisasi pembelajar. Para karyawan dan manajerial Anara Hotel Bandara telah berkomitmen untuk melakukan proses perubahan manajemen yaitu unfreezing-movement-refreezing. Para karyawan dan manajerial Anara Airport Hotel Bandara Soekarno Hatta sepakat untuk menjadi organisasi autentik, yaitu organisasi yang memiliki perilaku, struktur, dan proses, yang didasari oleh kemampuannya menemukan kesejatian dalam rangka mencapai tujuan yang ditetapkan oleh Manajemen Anara Airport Hotel Bandara Soekarno Hatta serta siap menghadapi perubahan lingkungan serta siap untuk berubah menjadi individu yang unggul dan pemimpin yang menjadi panutan bagi karyawan lainnya.